Fairness, Equity and Efficiency for the Convention on Biological Diversity and the Nagoya Protocol: Analysis of a Rodent, a Snail, a Sponge and a Virus. Part 1 - (SPDA), Sociedad Peruana de Derecho Ambiental (2022)
Case studies based on 4 different organisms to determine the best modality for ABS. We recommend that the Parties reaffirm the nature of the CBD and Nagoya Protocol (NP) as framework agreements. Decisions made at the COP can be revisited and reversed. The adoption of an alternative modality to bilateralism could even include a return to the “Common Heritage of Mankind” (Modality 5), which is just as much an expression of sovereignty as is the bilateral approach. Policy implications must be rendered into recommendations and the recommendations, into legislation. Appendix VI is a “Legal Elements for the ‘Global Multilateral Benefit-sharing Mechanism’ as contemplated in the Nagoya Protocol on Access to Genetic Resources and the Fair and Equitable Sharing of Benefits Arising from their Utilization”.